Semi-dry method for preparing high-strength network composite particles
Preparing high-strength network composite particles through a semi-dry method solves the problem of difficulty in separating montmorillonite from water, improves the strength and ease of separation of hydrogel composites, and achieves efficient treatment of organic pollutants in industrial wastewater. and heavy metal ions.
Patent Information
- Application Number
- CN202110998586.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-08-27
AI Technical Summary
In the prior art, the difficulty of separating montmorillonite from water as an adsorbent is the main limitation of its widespread application in industry, and hydrogels and their composites have low strength, easy damage, high cost when treating industrial wastewater. Problems with complex preparation process.
High-strength reticular composite particles are prepared by a semi-dry method, and polyvinyl alcohol aqueous solution and montmorillonite are cross-linked under the action of formaldehyde to prepare high-strength polyvinyl formal-montmorillonite composite particles.
It achieves a low loss rate of composite particles in water (0.2-1.5%), improves its adsorption and easy separation, reduces preparation costs, and is suitable for large-scale treatment of organic pollutants and heavy metal ions in water.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical materials and relates to a novel three-dimensional network of polyvinyl formal-montmorillonite composite particles with high strength and a preparation method thereof. Background Art
[0002] Wastewater treatment is a huge challenge in the production of industrial products (Pereira et al., 2021; Wei Zhang et al., 2021). Heavy metals and organic pollutants often remain in wastewater from various industries, such as metal plating, mining, paint, batteries, fertilizers, textiles, paper and pulp, paint, printing and cosmetics. The concentration of pollutants in industrial wastewater must be reduced to the allowable discharge limit before it can be discharged into the water body (Mahmud et al., 2016; Javadian et al., 2014; Samiey et al., 2014; Ying Chen et al., 2021). These industrial wastewaters are directly discharged into the environment without treatment or incomplete treatment, which will cause great harm to humans and the earth's ecosystem. In the past few decades, heavy metal ions and organic dyes have seriously harmed animals, plants and humans due to their non-biodegradability and bioaccumulation (Muhammad Jamlt et al., 2010; Singh et al., 2010; Ruo et al., 2017). Therefore, it is crucial to remove pollutants from industrial wastewater before it is discharged into water bodies.
[0003] Adsorption separation technology is widely used in wastewater treatment because of its simplicity and effectiveness (Yadav et al., 2019). The most widely used adsorption materials are clay (Yadav et al., 2019; Wang et al., 2018; AderonkeAjibolaAdeyemo et al., 2015), resin polymer (Wu et al., 2018), activated carbon (PornladaDaorattanachai et al., 2005) and zeolite (Ji Fei et al., 2012). In recent years, clay mineral materials have been widely studied and applied in wastewater treatment due to their good adsorption performance, harmlessness, low cost, easy availability and greenness, especially montmorillonite, which is more popular (Yadav et al., 2019).
[0004] Montmorillonite (Mt) is a typical 2:1 layered aluminum silicate, whose cathode layer is balanced by equally charged positive ions, such as Na + and Ca 2+(Bardziński00 et al., 2014; Lagaly et al., 2013). Due to its excellent properties such as high cation exchange capacity (CEC), swelling in water and large adsorption capacity, it has attracted widespread attention (Guanzheng Zhuang et al., 2015). Mt has a wide range of applications in casting, pelletizing, slurry, soil improvement, food processing, medicine and daily chemical industries (Jiarui Cui et al., 2020; Guanzheng Zhuang et al., 2016). In particular, due to its excellent adsorption performance for organic pollutants and heavy metal ions, Mt has important application prospects in the field of sewage treatment (Vijay Bahadur Yadav et al., 2019). Many studies on the use of Mt to remove various metal ions and organic dyes have been reported in the literature. Researchers have studied the effect of Mt on Pb 2+ The adsorption performance of Mt for Pb2+ can reach 28 mg / g (De Pablo et al., 2011). At the same time, many researchers have studied the adsorption of Cu on Mt. 2+ 、Cd 2+ Cr 3+ 、Ni 2+ , Mn 2+ 、Zn 2+ , Hg 2+ and Ba 2+ etc. (Yang et al., 2015; Wu et al. 2011; Kumar et al., 2011; Akpomie and Dawodu, et al., 2014; Ijagbemi et al., 2009; Bhattacharyya and Gupta et al., 2007). In recent years, the adsorption of industrial organic dyes by Mt and Mt composites has also attracted widespread interest (Mohamed Shaban et al., 2017; Momina et al., 2018; Huawen Han et al., 2019; Min-Yun Chang et al., 2004).
[0005] The difficulty in separating Mt from water as an adsorbent is the main problem that limits its widespread application in industry. In addition, in the process of wastewater treatment, due to its small size, especially because of its excellent gel properties, Mt is very easy to form a cell structure after dispersion in water, making it very difficult to separate it from the water body (Jiarui Cui et al., 2020). Therefore, it is very easy to cause secondary environmental pollution. Hydrogels are cross-linked three-dimensional network polymers that can swell rapidly and retain a large amount of water in their swollen structure. They are usually composed of hydrophilic polymers, which are cross-linked by chemical bonds or other cohesive forces (such as ionic effects, hydrogen bonds or hydrophobic effects) to form a three-dimensional network structure (Holback et al., 2011; Muya et al., 2016; Buengeret et al., 2012; Abeer et al., 2014; Liu et al., 2014). There are also many reports on the application of various hydrogels and their composites in the treatment of heavy metal ions and organic dye pollutants (Bharskar et al., 2020; Jianyu Xing et al., 2020; Muya et al., 2016; Antonio et al., 2021; Liu et al., 2014; Yan et al., 2004). However, hydrogels and their composites have problems such as low strength, easy breakage, high cost and complex preparation process, which greatly limits their treatment and application in industrial wastewater. Summary of the invention
[0006] In order to overcome the above problems, the inventors have conducted a keen study on the separation of clay mineral adsorption materials and water bodies, and developed a method for preparing high-strength network composite particles by a semi-dry method. The polyvinyl alcohol aqueous solution and montmorillonite are cross-linked under the action of formaldehyde to prepare high-strength network polyvinyl alcohol formal-montmorillonite composite particles. Since both polyvinyl alcohol and montmorillonite contain free hydroxyl groups, they react with the aldehyde acetal in formaldehyde to give the composite particles the characteristics of high strength, strong adsorption, and easy separation, and are very practical. The loss rate of the prepared composite particles in water is only 0.2-1.5%, which is suitable for large-scale adsorption treatment of organic pollutants and heavy metal ions in water; and since the content of montmorillonite in the prepared composite particles is 80-90wt%, which is much greater than the content of the polyvinyl alcohol formal polymer contained, the preparation cost is low, and it has obvious economic and social benefits, thereby completing the present invention.
[0007] Specifically, the purpose of the present invention is to provide the following aspects:
[0008] In a first aspect, high-strength network composite particles are provided, wherein the composite particles are polyvinyl formal-clay mineral composite particles.
[0009] In a second aspect, a method for preparing high-strength network composite particles is provided, the method comprising the following steps:
[0010] Step 1, preparing a polymer aqueous solution;
[0011] Step 2, blending the polymer aqueous solution, the cross-linking agent and the clay mineral, and treating them to obtain a composite material;
[0012] Step 3, subjecting the composite material to a cross-linking reaction.
[0013] In a third aspect, there is provided an application of the high-strength network composite particles described in the first aspect or the high-strength network composite particles obtained according to the preparation method described in the second aspect in treating organic pollutants or heavy metal ions in water.
[0014] The beneficial effects of the present invention include:
[0015] (1) The high-strength network composite particles provided by the present invention have a loss rate of only 0.2-1.5% in water, and are suitable for large-scale adsorption treatment of organic pollutants and heavy metal ions in water.
[0016] (2) The content of montmorillonite in the high-strength network composite particles provided by the present invention is 80-95wt%, which is much greater than the content of the polyvinyl formal polymer contained therein, and the preparation cost is low, with obvious economic and social benefits.
[0017] (3) The preparation method of the high-strength network composite particles provided by the present invention uses polyvinyl alcohol as a matrix and montmorillonite as a filler to obtain high-strength network composite particles through cross-linking. Without changing the original performance of polyvinyl alcohol, its water resistance and barrier to water vapor are improved, and its dependence on water content is reduced. At the same time, the problem of the difficulty in separating montmorillonite from water as an adsorbent is solved.
[0018] (4) The method for preparing high-strength network composite particles provided by the present invention has the characteristics of high strength, strong adsorption and easy separation, because both polyvinyl alcohol and montmorillonite contain free hydroxyl groups, which react with the aldehyde acetal in formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A process diagram showing the removal of methylene blue by PVAM-Mt and Mt in Experimental Example 2 is shown;
[0020] Figure 2 The XRD pattern in Experimental Example 3 is shown;
[0021] Figure 3 The FTIR graph in Experimental Example 4 is shown;
[0022] Figure 4 The SEM characterization picture of Experimental Example 5 is shown. DETAILED DESCRIPTION
[0023] The present invention will be further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present invention will become more clear and distinct.
[0024] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0025] In one aspect, the present invention provides high-strength network composite particles, wherein the composite particles are polyvinyl formal-clay mineral composite particles, have a network structure, and are easily separated from water.
[0026] Furthermore, the content of polyvinyl formal in the composite particles is 10-20wt%, preferably 11-15wt%, for example 12wt%; the content of clay mineral in the composite particles is 80-90wt%, preferably 85-89wt%, for example 88wt%.
[0027] According to the present invention, the clay mineral in the composite particles is a layered silicate, preferably selected from any one or more of talc, muscovite, montmorillonite, sepiolite, and vermiculite, more preferably montmorillonite.
[0028] Furthermore, when the clay mineral in the composite particles is montmorillonite, the composite particles have a -1 , 3365cm -1 , 1634cm -1 , 1430cm -1 There is a montmorillonite absorption peak at 2942cm -1 、2894cm -1 、3276cm -1 There are -CH2, -CH3 and -OH absorption peaks of polyvinyl alcohol respectively.
[0029] The particle size of the composite particles is 1 mm to 20 mm, preferably 3 mm to 12 mm, and more preferably 4 mm to 10 mm.
[0030] According to the present invention, the composite particles have high strength, and the loss rate in water is lower than 2.5%, preferably 0.2-1.5%, and more preferably 0.5-1.0%.
[0031] In the present invention, the composite particles are prepared using polymer, clay mineral and cross-linking agent as raw materials.
[0032] In another aspect, the present invention provides a method for preparing the high-strength network composite particles described above, comprising the following steps:
[0033] Step 1, preparing a polymer aqueous solution.
[0034] In step 1, a linear polymer is dissolved in water to prepare a polymer aqueous solution.
[0035] The linear polymer is preferably selected from any one or more of polyvinyl alcohol, polyacrylic acid, polyacrylonitrile and polyacrylamide, and is more preferably polyvinyl alcohol.
[0036] According to the present invention, the linear polymer has a strictly regular linear structure, the prepared composite particles have a uniform structure, and due to the weak binding force between the linear polymer and the clay mineral, in the subsequent cross-linking process, the linear polymer is not sufficient to completely enter between the clay minerals or adsorb the clay minerals.
[0037] Furthermore, polyvinyl alcohol is used as a linear polymer. The polyvinyl alcohol is an important water-soluble polymer material. It contains a large number of free hydroxyl groups in the molecule, forming a large number of intramolecular and intermolecular hydrogen bonds, and therefore has high crystallinity, chemical stability, thermal stability, light transmittance, good gloss and high mechanical strength. In addition, polyvinyl alcohol is a water-soluble and biodegradable polymer.
[0038] In step 1, the dissolution temperature of polyvinyl alcohol in water is 70-95° C., preferably 80-92° C., and more preferably 85-90° C. At this time, the polyvinyl alcohol can be dissolved quickly while preventing discoloration and embrittlement.
[0039] In step 1, the concentration of the linear polymer in the prepared polymer aqueous solution is 0.3 to 1.5 g / mL, preferably 0.5 to 1.2 g / mL, and more preferably 0.7 to 0.8 g / mL.
[0040] Step 2: blending the polymer aqueous solution, the cross-linking agent and the clay mineral, and treating them to obtain a composite material.
[0041] In step 2, the cross-linking agent is preferably an aldehyde compound such as formaldehyde, acetaldehyde, a diamine compound such as ethylenediamine, hexamethylenediamine, an amide compound such as acrylamide or a carboxylic acid compound such as acetic acid, acrylic acid, etc., more preferably an aldehyde compound, such as formaldehyde.
[0042] According to the present invention, aldehyde compounds are used as cross-linking agents to effectively improve the water resistance and mechanical properties of the prepared composite particles, and in particular, formaldehyde is used as the cross-linking agent to improve the performance more effectively.
[0043] In step 2, the clay mineral is a layered silicate, preferably selected from any one or more of talc, muscovite, montmorillonite, sepiolite, and vermiculite, such as montmorillonite.
[0044] In step 2, a strong acid is also added during blending. The strong acid is preferably an inorganic acid, such as hydrochloric acid, sulfuric acid, nitric acid, etc., more preferably hydrochloric acid, such as concentrated hydrochloric acid with a concentration of 12 mol / L.
[0045] In the present invention, the weight ratio of the linear polymer, the crosslinking agent and the clay mineral is (3-9):1:(60-90), preferably (5.5-7):1:(65-80), and more preferably (6-6.3):1:(70-71).
[0046] Further, the weight of the linear polymer is related to the strong acid (in terms of H + The molar ratio (in terms of moles) is (0.1-2) g: (1-5) mmol, preferably (0.3-1) g: (2-3) mmol, more preferably (0.6-0.8) g: (2.0-2.5) mmol, for example 0.7 g: 2.4 mmol.
[0047] In the present invention, during the cross-linking reaction, the polymer aqueous solution and the clay mineral react with the cross-linking agent under the catalysis of a strong acid. As the amount of the cross-linking agent increases, the tensile strength and mechanical strength of the prepared composite particles both show an increasing trend. However, an excessive amount of cross-linking agent causes the final composite material to be in a gel state, making it impossible to granulate. Even if composite particles can be prepared, their water absorption rate will be significantly reduced. This may be because an excessive amount of cross-linking agent forms a large number of network structures through cross-linking, which severely limits the activity space of linear polymers such as polyvinyl alcohol molecules, making them less likely to absorb water and swell. In addition, due to the low content of hydroxyl groups in the polyvinyl alcohol formal in the composite particles, the hydrophobicity increases, and the performance of removing organic pollutants or heavy metal ions in sewage is reduced.
[0048] According to the dosage ratio of polymer aqueous solution, cross-linking agent, clay mineral and strong acid, when blended, the above substances form not a liquid state, but a viscous state, similar to a "mud" state, which is called a semi-dry state.
[0049] The semi-dry state is conducive to granulating the uniformly blended materials to obtain a composite material with uniform size and high strength.
[0050] In step 2, the treatment includes stirring and granulation.
[0051] The granulation is to prepare the uniformly stirred blend into a composite material with uniform particle size, and the particle size of the composite material is 1 mm to 20 mm, preferably 3 mm to 12 mm, and more preferably 4 mm to 10 mm.
[0052] Step 3, subjecting the composite material to a cross-linking reaction.
[0053] In step 3, the temperature of the cross-linking reaction is 40-90°C, preferably 50-85°C, more preferably 55-80°C, for example 60°C; the time of the cross-linking reaction is 60-240 min, preferably 80-180 min, preferably 90-150 min, for example 100 min.
[0054] In the present invention, the linear polymers such as polyvinyl alcohol and clay minerals such as montmorillonite contain free hydroxyl groups, which undergo acetalization reaction and cross-linking with the aldehyde groups in the cross-linking agent aldehyde compounds. Since the amount of aldehyde compounds such as formaldehyde used is small, the polyvinyl alcohol formal in the prepared composite particles still maintains good hydrophilicity, which is extremely beneficial for the removal of organic pollutants or heavy metal ions in sewage.
[0055] During cross-linking, strong acid acts as a catalyst in the cross-linking reaction. Under the catalytic action of strong acid, the cross-linking reaction temperature and time are controlled to facilitate the reaction. Due to the aldehyde group in the aldehyde compound, the linear polymer molecular chains, the clay minerals, and the linear polymer molecular chains and the clay minerals are interconnected to form a network structure, which improves the mechanical strength of the composite particles.
[0056] In another aspect, the present invention provides use of the high-strength network composite particles described in the first aspect or the high-strength network composite particles obtained according to the preparation method described in the second aspect in treating organic pollutants or heavy metal ions in water.
[0057] Furthermore, the high-strength mesh composite particles have an excellent removal effect on cationic organic dyes and heavy metal ions in water, with a removal rate of more than 98% for cationic organic dyes in water and a removal rate of more than 95% for heavy metal ions in water.
[0058] In the present invention, although the linear polymer such as polyvinyl alcohol has many characteristics such as good chemical stability, thermal stability, light transmittance, good gloss, high mechanical strength, degradability, etc., its water vapor permeability and water absorption are too large, and its mechanical properties are greatly affected by temperature and water content. The existing modification technology has not been able to fundamentally solve the problem, which is not conducive to promotion and application. Its own characteristics are more limited to the preparation of films or powders, and it is impossible to carry out processing techniques such as blow molding, which seriously limits its practicality.
[0059] In addition, when the conventional process uses linear polymers such as polyvinyl alcohol and layered silicates such as montmorillonite to prepare thin films or powders, the content of linear polymers in the prepared thin films or powders is much higher than that of layered silicates, and the preparation cost is very high because the layered silicates are completely modified and mainly used as dispersants in the process. In terms of the application of treating organic pollutants or heavy metal ions, the high content of linear polymers and their strong dispersibility in pollutants, which in turn leads to higher suspension in pollutants, ultimately make the dispersibility of layered silicates and the final separation process very difficult.
[0060] In the present invention, a linear polymer such as polyvinyl alcohol is used as a matrix, and a layered silicate such as montmorillonite is used as a filler, and high-strength network composite particles are prepared by cross-linking. Without changing the original performance of the linear polymer, the water resistance and water vapor barrier of the linear polymer are improved, stable mechanical properties are obtained, and the dependence of the linear polymer on water content is reduced. At the same time, the problem of the difficulty in separating montmorillonite from water as an adsorbent is solved, and the comprehensive performance of the linear polymer and the layered silicate is fundamentally improved. When applied to treat organic pollutants and heavy metal ions, due to its very low loss rate in water, excellent mechanical strength, and easy separation, the composite particles adsorbed with pollutants can be separated from the water body by direct separation, and the practicability is very strong.
[0061] The present invention is further described in detail below by way of examples.
[0062] Example
[0063] Example 1 Preparation of PVAM-Mt
[0064] 0.7 g of polyvinyl alcohol (PVA) and 8 mL of water were placed in a reactor, and the polyvinyl alcohol was dissolved by stirring at 90° C. to obtain 10 ml of a polyvinyl alcohol aqueous solution, which was then cooled.
[0065] Afterwards, 8 g of montmorillonite (Mt) powder, 0.3 mL of 38% formaldehyde solution and 0.2 mL of 12 mol / L concentrated hydrochloric acid were added to the above reactor, and then granulated into a composite material with a particle size of 5 to 10 mm. The composite material was placed in an oven and cross-linked at 60°C for 100 minutes, then taken out and cooled to obtain high-strength network composite particles PVAM-Mt.
[0066] Comparative Example
[0067] Comparative Example 1
[0068] 8 g of Mt powder was mixed with 8 mL of water, and granulated into a material with a particle size of 5 to 10 mm. The material was placed in an oven, dried at 60° C. for 100 min, and then taken out and cooled to obtain Mt particles.
[0069] Experimental example
[0070] Experimental Example 1 Mechanical strength test of PVAM-Mt and Mt particles in water
[0071] (1) Weigh 2.23 g (m1) of PVAM-Mt prepared in Example 1 and add it to 50 mL of water. Oscillate at a constant temperature of 30°C for 24 h, then let it stand for 120 min. Use a spoon to scoop out the PVAM-Mt to separate it from the water. Dry the separated PVAM-Mt at a constant temperature of 60°C for 24 h, and weigh it to 2.21 g (m2) after cooling and keeping the temperature constant. Calculate the loss rate (ω) of PVAM-Mt according to formula (1), and use ω to characterize the strength of PVAM-Mt.
[0072]
[0073] Where:
[0074] m1 is the mass of the substance weighed before oscillation,
[0075] m2 is the mass of the substance measured after cooling to constant temperature.
[0076] (2) Weigh 8 g (m1) of the Mt particles obtained in Comparative Example 1 and add them to 50 mL of aqueous solution. Oscillate at a constant temperature of 30°C for 24 h, then let stand for 120 min, filter and separate, and dry the separated Mt particles at a constant temperature of 60°C for 24 h. After cooling and keeping the temperature constant, weigh 1.5 g (m2). Calculate the loss rate (ω) of the Mt particles according to formula (1).
[0077] After calculation, the loss rate of PVAM-Mt prepared in Example 1 in water is 0.90%, and the loss rate of Mt particles prepared in Comparative Example 1 in water is 70%, indicating that PVAM-Mt has high mechanical strength in water. After the PVAM-Mt prepared in Example 1 is allowed to stand in water for 120 minutes, it can be separated from water directly with a spoon, indicating that it is easy to separate from water. The mechanical strength of Mt particles in water is very poor, and they are directly dispersed when encountering water. Most of them are dissolved in water and are difficult to be directly separated from water.
[0078] Experimental Example 2 Effects of PVAM-Mt and Mt on methylene blue and Pb 2+ Removal rate
[0079] 1) PVAM-Mt for methylene blue (MB) and Pb 2+ Removal rate
[0080] Weigh the mass m of PVAM-Mt prepared in Example 1 and add it to a 50 mL volume of methylene blue (or Pb 2+) solution, at 30°C, constant temperature oscillation for 90 min, standing for 60 min to complete adsorption, obtain supernatant, then scoop out PVAM-Mt directly with a spoon to separate it from water, dry the adsorbed PVAM-Mt, weigh the mass and record it as m2. 2+ The maximum absorption wavelengths of the supernatant were 665nm and 560nm respectively, and the residual methylene blue (or Pb 2+ ) concentration C1. According to formula (2) and formula (3), the PVAM-Mt to methylene blue (or Pb 2+ ) removal rate μ and adsorption amount Q e .
[0081]
[0082]
[0083] 2) Mt to methylene blue and Pb 2+ Removal rate
[0084] In a similar manner to 1) above, Mt powder was used to react with methylene blue and Pb 2+ The difference is that after adsorption, the supernatant is obtained by high-speed centrifugation at 10,000 r / min for 15 min and then allowed to stand for 60 min. The supernatant is measured by spectrophotometry for methylene blue (or Pb 2+ ) absorbance, calculate the residual methylene blue (or Pb 2+ ) concentration C1. Calculate the concentration of Mt powder to methylene blue solution (or Pb 2+ ) removal rate μ and adsorption amount Q e .
[0085] The above-mentioned PVAM-Mt and Mt powders have a great influence on the performance of methylene blue and Pb 2+ The removal results are shown in Table 1 and Table 2:
[0086] Table 1 Removal of methylene blue by Mt powder and PVAM-Mt
[0087]
[0088] Table 2 Effect of Mt powder and PVAM-Mt on Pb 2+ Removal
[0089]
[0090] As shown in Table 1, after PVAM-Mt treated 300 mg / L methylene blue solution, the methylene blue concentration dropped to 3.02 mg / L, the removal rate μ of methylene blue reached 98.99%, and the adsorption capacity Qe Reaching 20.07mg / g, better than Mt powder (μ = 96.38%, Q e =19.28 mg / g) and is easy to separate, and the adsorption capacity of PVAM-Mt for 1000 mg / L methylene blue reaches 60.14 mg / g.
[0091] It can be seen from Table 2 that PVAM-Mt has a significant effect on Pb 2+ The removal rate μ reached 95.45%, and the adsorption capacity Q e Reaching 19.15mg / g, better than Mt powder (μ=92.00%,Q e =18.40 mg / g), PVAM-Mt to 1000 mg / L Pb 2+ The adsorption capacity reached 61.56 mg / g.
[0092] Figure 1 -(1) is a diagram showing the process of removing methylene blue (MB) from water by the above-mentioned Mt powder, Figure 1 -(2) shows the process diagram of the above PVAM-Mt removing methylene blue, and it is obvious from the figure:
[0093] Figure 1 -(1) Mt adsorbed with methylene blue is suspended in the system in a dark blue color, which is basically the same as the solution without methylene blue adsorption, such as Figure 1 -(1) As shown in A and C, even after high-speed centrifugation, the clarity of the supernatant ( Figure 1 -(1)D) is still higher than that of the sample treated with PVAM-Mt ( Figure 1 -(2)d) is poor, and there is still a lot of Mt suspended in the water.
[0094] Figure 1 -(2)e is the PVAM-Mt fished out after PVAM-Mt adsorbed methylene blue, which appeared dark blue; Figure 1 -(2)d is the water sample after PVAM-Mt adsorbed and removed methylene blue, and the water sample is clear and transparent; this process shows that PVAM-Mt has high adsorption efficiency for methylene blue and is easy to operate.
[0095] Experimental Example 3 Crystal structure of PVAM-Mt
[0096] XRD analysis was performed on Mt powder (hereinafter referred to as Mt), wet Mt, PVAM-Mt prepared in Example 1, and wet PVAM-Mt using a D8Advance X-ray diffractometer produced by Bruker Scientific Instruments Hong Kong CO., Limited. The experimental conditions were: Cu target, ceramic X-ray tube (2.2 kW), rated voltage 60 KV, rated current 80 mA, step size 0.02°, and scanning angle range 3° to 70°.
[0097] The results are as follows Figure 2 As shown in the figure, it can be seen that: Mt 001 The value is 1.20nm, d 010 The d of PVAM-Mt is 0.45nm. 001 The value is 1.40nm, slightly larger than that of Mt raw material (1.20nm); d 010 It is 0.45 nm, indicating that PVAM-Mt maintains the structural characteristics of Mt, and some polymers enter the interlayer of Mt.
[0098] Wet Mt retains Mt 001 and 010 surfaces, d 001 The value is 1.50nm, d 010 0.45nm; wet PVAM-Mt still retains Mt 001 and 010 surfaces, and its d 001 The value is 1.84nm, which is larger than the wet state Mt,d 010 The results show that the Mt interlayers in the wet PVAM-Mt contain polymers and water molecules, and the Mt in the PVAM-Mt still absorbs water and swells, so PVAM-Mt has excellent water absorption and swelling properties, excellent interlayer cation exchange capacity, and better adsorption performance for pollutants than Mt raw materials.
[0099] Experimental Example 4 The network structure of PVAM-Mt
[0100] The infrared spectrometer model Thermo Nicolet 6700 was used in the wave number range of 800 to 4000 cm -1 、Resolution ratio is 4~8cm -1 , under the condition of Scan number 32, Mt powder (hereinafter referred to as Mt), polyvinyl alcohol and PVAM-Mt prepared in Example 1 were tested.
[0101] The results are as follows Figure 3As shown in the figure, it can be seen that in the infrared spectrum curve of Mt, the Al-OH stretching vibration and the OH stretching vibration absorption peaks of interlayer water molecules are at 3618 cm -1 and 3365cm -1 1634cm -1 The absorption peak is the bending vibration of Al-OH of Mt and -OH of interlayer water molecules. -1 The absorption peak is the Si-O-Si stretching vibration of Mt. In the infrared spectrum curve of PVA, 3276cm -1 The characteristic absorption peak of -OH of PVA is 2942cm -1 and 2894cm -1 The absorption peaks of PVA are -CH2 and -CH3. Therefore, in addition to 3618cm -1 , 3365cm -1 , 1634cm -1 , 1430cm -1 In addition to the absorption peak attributed to Mt, there are also the absorption peaks of -CH2 and -CH3 of PVA at 2942 cm -1 and 2894cm -1 , indicating that the main components of the composite sample are Mt and PVA. In addition, PVAM-Mt still retains the 3276cm -1 Characteristic peaks: PVA in PVAM-Mt has an appropriate amount of -OH, but the amount of -OH is significantly less than that of PVA, indicating that a cross-linking reaction occurred between PVA and formaldehyde.
[0102] Experimental Example 5 Morphological characterization of PVAM-Mt
[0103] The morphology of Mt and the PVAM-Mt prepared in Example 1 was observed using a JSM-IT300 scanning electron microscope (SEM) with a voltage of 100 V, a load current of 13 A, and a frequency of 50 / 60 Hz.
[0104] The results are as follows Figure 4 As shown, it can be seen that the surface of PVAM-Mt has obvious pores and grooves, which are conducive to the adsorption of pollutants.
[0105] Experimental Example 6 Zeta Potential of PVAM-Mt
[0106] Zetasizer Nano Zeta potential analyzer produced by Malvern Instruments Ltd., UK, was used to perform Zeta test on Mt powder (hereinafter referred to as Mt) and PVAM-Mt prepared in Example 1. The results are shown in Table 3. It can be seen that the Zeta potential value of Mt is -24.5mV, the Zeta potential value of PVAM-Mt is -22.7mV, and the Zeta potential value of PVAM-Mt is not much different from that of Mt, which is basically equivalent. Therefore, Mt in PVAM-Mt basically retains its original negative charge and has strong adsorption to pollutants.
[0107] Table 3 Zeta potential values of PVAM-Mt and Mt
[0108]
[0109] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.
Claims
1. A semi-dry method for preparing high-strength network composite particles, characterized in that: The method comprises the following steps: Step 1, preparing a polymer aqueous solution; Step 2, blending the polymer aqueous solution, the cross-linking agent and the clay mineral, and treating them to obtain a composite material; Step 3, subjecting the composite material to a cross-linking reaction; The composite particles are polyvinyl formal-clay mineral composite particles. The content of polyvinyl formal in the composite particles is 11-15wt%, and the content of clay mineral is 85-89wt%. The particle size of the composite particles is 1 mm to 20 mm. In step 1, a linear polymer is dissolved in water to obtain a polymer aqueous solution having a linear polymer concentration of 0.5 to 1.2 g / mL, wherein the linear polymer is selected from polyvinyl alcohol, In step 2, the cross-linking agent is formaldehyde, and the clay mineral is selected from montmorillonite. In step 2, a strong acid is added during blending, wherein the strong acid is hydrochloric acid, sulfuric acid, or nitric acid. In step 3, the temperature of the cross-linking reaction is 50-90° C., and the time of the cross-linking reaction is 60-240 min.
2. The method according to claim 1, characterized in that The loss rate of the composite particles in water is less than 2.5%.
3. The method according to claim 2, characterized in that The loss rate of the composite particles in water is 0.2-1.5%.
4. The method according to claim 1, characterized in that: In step 1, a polymer aqueous solution with a linear polymer concentration of 0.7 to 0.8 g / mL is prepared.
Citation Information
Patent Citations
Method of preparing high performance three-dimensional network adsorbent by semi-dry method
CN109482158A
Bentonite / polymer adsorption particles with grid structure and preparation method thereof
CN113134346A